Multiple Sclerosis and COVID-19: An Overview on Risk, Severity, and Association With Disease Modifying Therapies - Mary Hollist; Abraham Hollist; Katherine Au; Colton Betts; Maha Kirmani; Maaida Kirmani; Benjamin Armour; Mercy C Udeh; Batool F Kirmani (Neuroscience Insights)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a novel coronavirus, emerged in December 2019, sparking a global health crisis. While initially recognized as a respiratory illness, it has become evident that Coronavirus disease 2019 (COVID-19) also affects the central nervous system. This comprehensive review focuses on the neurological manifestations of COVID-19 and its impact on patients with preexisting neurological disorders, particularly those with multiple sclerosis (MS) receiving disease-modifying therapies. Advancements in management, including vaccinations, antiviral therapy, and targeted prophylaxis, have led to a decline in the incidence and severity of COVID-19. Nevertheless, significant complications persist, particularly in patients with advanced MS, who are highly vulnerable to infectious agents like SARS-CoV-2. This review explores the evolving understanding of MS and its association with SARS-CoV-2, encompassing neuroinvasiveness, pathogenesis, disease severity, and outcomes. Research findings reveal substantial neurological implications for some MS patients with COVID-19, with a potential risk of disease relapse and severity. A notable proportion of MS patients experiencing COVID-19 may manifest new symptoms, experience exacerbation of existing symptoms, or encounter both simultaneously, underscoring the diverse neurological effects of the virus. While vaccination and therapeutics have mitigated the overall impact, specific subgroups, especially those on anti-CD20 therapy and with existing disability, remain at higher risk, necessitating ongoing vigilance and tailored care.